LEVEL OF PHYSICAL ACTIVITY IN ELDERLY POPULATION OF RAWALPINDI- ISLAMABAD - Ramsha Sohail; Abdul Haseeb Bhutta; Nayab Asif; Qurat Ul Ain (The Rehabilitation Journal, 2018)
Objective: To find out the level of physical activity in elderly population. Methods: a cross- sectional survey was conducted in Rawalpindi and Islamabad. The sample size of the study was n=165 elders who fulfill the inclusion criteria were included in the study. Non-probability convenience sampling was used in order to collect data from the respondents. To explore physical activity Rapid Assessment of Physical Activity (RAPA) questionnaire was filled by the respondents. The results of study are presented as frequency, percentages; mean±SD. SPSS ver. 21 was used for data analysis. Results: A total of 26(15.76%) elderly population were sedentary, 24(14.55%) were under active-perform light to moderate activities but not every week , 58(35.15%) were under active, 31(18.79%) were also under active and perform moderate physical activities every week, 21(12.73%) were active and perform moderate physical activities>30 minutes/day, 5 or more days a week and only 2(1.21%) were active and perform vigorous physical activities >20 minutes/day, 3 or more days a week. Conclusion: The result indicates that majority of geriatric population was under active. The elderly population who had sedentary lifestyle and who were active had the same prevalence. Keywords: Elderly population, physical activity, sedentary